2022
DOI: 10.1098/rsos.211718
|View full text |Cite
|
Sign up to set email alerts
|

The effect of attention on body size adaptation and body dissatisfaction

Abstract: Attentional bias to low-fat bodies is thought to be associated with body dissatisfaction—a symptom and risk factor of eating disorders. However, the causal nature of this relationship is unclear. In three preregistered experiments, we trained 370 women to attend towards either high- or low-fat body stimuli using an attention training dot probe task. For each experiment, we analysed the effect of the attention training on (i) attention to subsequently presented high- versus low-fat body stimuli, (ii) visual ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 78 publications
(128 reference statements)
1
8
0
Order By: Relevance
“…The absence of association between body dissatisfaction and attentional bias to thin bodies contrasts with certain dot probe studies that report a positive association [3133]. However, the results are consistent with other dot probe studies that found no evidence for an association [3335].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The absence of association between body dissatisfaction and attentional bias to thin bodies contrasts with certain dot probe studies that report a positive association [3133]. However, the results are consistent with other dot probe studies that found no evidence for an association [3335].…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, a laboratory setting may be necessary to detect this positive association. However, other dot probe studies conducted in a laboratory setting failed to find evidence for an association [3335], and one study found similar results regardless of whether the study was completed online or in a laboratory setting [35]. Therefore, a laboratory setting is certainly not a sufficient condition for detecting a positive association.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations